1973
DOI: 10.1093/geront/13.2.215
|View full text |Cite
|
Sign up to set email alerts
|

The Older Adult Volunteer Compared to the Nonvolunteer

Abstract: Characteristics of older adult volunteers and nonvolunteers who were active in a community center's programs were compared in order to determine correlates of voluntarism. Only two variables significantly differentiated: sex and past patterns of organizational participation. Findings suggest a high degree of consistency between past and present activity patterns of older adults. Implications related to pre-retirement planning and to the appropriate placement of the elderly in post-retirement activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 5 publications
1
15
0
Order By: Relevance
“…In terms of our interests here, two overlapping patterns have been described. First, there is a contention that older persons' membership in voluntary associations tapers off, and that they are less likely to belong to or be affiliated with voluntary associations than their younger counterparts (Chambré, 1984(Chambré, , 1993Dye, Goodman, Roth, Bley, & Jensen, 1973;Monk, 1995). At the same time, the relationship between age and voluntary association participation has been described as curvilinear, reflecting time and resources available to people of differing ages (Cutler, 1976;Herzog & Morgan, 1993).…”
mentioning
confidence: 99%
“…In terms of our interests here, two overlapping patterns have been described. First, there is a contention that older persons' membership in voluntary associations tapers off, and that they are less likely to belong to or be affiliated with voluntary associations than their younger counterparts (Chambré, 1984(Chambré, , 1993Dye, Goodman, Roth, Bley, & Jensen, 1973;Monk, 1995). At the same time, the relationship between age and voluntary association participation has been described as curvilinear, reflecting time and resources available to people of differing ages (Cutler, 1976;Herzog & Morgan, 1993).…”
mentioning
confidence: 99%
“…It might be that a person's past interest, attitudes, and activities continue through life (Dye et al 1973). This finding is noteworthy in the sense that it can aid in the argument for the relative weakness of age effect in predicting volunteering activities over the life course.…”
Section: Age and Individual Community Involvementmentioning
confidence: 99%
“…One major concern of this research has been the differences between elderly volunteers and non-volunteers. A num ber of authors indicate no difference between older volunteers and non volunteers with regard to life satisfaction or morale (Carp, 1968;Dye et al, 1973;Bull and AuCoin, 1975). Although research has shown the direct relationship between socio-economic factors and volunteering, specific data on the socio-economic backgrounds of elderly volunteers is not available.…”
Section: The Elderly Volunteermentioning
confidence: 99%